DIALOG DAN TOLERANSI (SEBUAH ALTERNATIF DAKWAH DI TENGAH PLURALITAS AGAMA) - Farichatul Maftuchah (Komunika, 2017)
Religious plurality potentially can causes collisions, conflicts, violence and anarchic attitude among people who have different faiths. This is because every religion has the exclusive aspect in the form of truth claims, namely the recognition that their religion is the correct one, whereas any religion embraced by different people is wrong. Pluralism should be understood not only by knowing its existence, but also by real and active participation towards the plurality. To foster peace in this era of plurality, one of the workable alternatives is to build tolerance through dialogue. A pluralist should interact with a variety of religions with open mind, learning and respecting his/her dialogue partners as well as showing a commitment to his/her own religion in order to avoid relativism in religion.